PET imaging of neural activity, β-amyloid, and tau in normal brain aging. - Zhang, Kai; Mizuma, Hiroshi; Zhang, Xiaohui; Takahashi, Kayo; Jin, Chentao; Song, Fahuan; Gao, Yuanxue; Kanayama, Yousuke; Wu, Yuping; Li, Yuting; Ma, Lijuan; Tian, Mei; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2021)
Normal brain aging is commonly associated with neural activity alteration, β-amyloid (Aβ) deposition, and tau aggregation, driving a progressive cognitive decline in normal elderly individuals. Positron emission tomography (PET) with radiotracers targeting these age-related changes has been increasingly employed to clarify the sequence of their occurrence and the evolution of clinically cognitive deficits. Herein, we reviewed recent literature on PET-based imaging of normal human brain aging in terms of neural activity, Aβ, and tau. Neural hypoactivity reflected by decreased glucose utilization with PET imaging has been predominately reported in the frontal, cingulate, and temporal lobes of the normal aging brain. Aβ PET imaging uncovers the pathophysiological association of Aβ deposition with cognitive aging, as well as the potential mechanisms. Tau-associated cognitive changes in normal aging are likely independent of but facilitated by Aβ as indicated by tau and Aβ PET imaging. Future longitudinal studies using multi-radiotracer PET imaging combined with other neuroimaging modalities, such as magnetic resonance imaging (MRI) morphometry, functional MRI, and magnetoencephalography, are essential to elucidate the neuropathological underpinnings and interactions in normal brain aging.